The effect of gender on heart rate variability in asthmatic and normal healthy adults - Lutfi, Mohamed Faisal; Sukkar, Mohamed Yosif (International Journal of Health Sciences, 2011)
Objective: Low heart rate variability (HRV) has been identified as a strong predictor of a large number of diseases, reflecting the vital role of autonomic nervous system in maintaining health. It has been hypothesized that the gender differences in autonomic modulation may explain the gender differences in morbidity and/or mortality rate. This study aims to compare the autonomic modulation of males with that of females based on short-term HRV analysis. Materials and Methods: This cross sectional case-control study involved eighty males matched with seventy-six females. The age M±SD is 28.5±5.4 years in males and 27.3±5.6 years in females. Biocom 3000 ECG recorder was used for studying HRV. Data was analyzed using SPSS Software (v.17), screening studied variables for significant differences in the means between the groups was performed using unpaired t test. Mean heart rate (MHR) was introduced as a covariate in the statistical analysis of HRV using general linear model. Results: All short-term HRV (5-min) time domain indices, total power (TP), very low frequency (VLF), low frequency (LF) and high frequency (HF) components of frequency domains were significantly higher in males except MHR, which was significantly higher in females (P<0.05 for all). Conclusion: Global autonomic activity was higher in males. In contrast, females have higher heart rate compared with males. Key Words: heart rate variability, gender, autonomic